Utility of a Non-Exercise VO2max Prediction Model for Designing Ramp Test Protocols - Cunha, F. A.; Midgley, A.; Montenegro, R.; Vasconcellos, F.; Farinatti, P. (International Journal of Sports Medicine, 2015)
This study investigated the validity of determining the final work rates of cycling and walking ramp-incremented maximal cardiopulmonary exercise tests (CPETs) using a non-exercise model to predict maximal oxygen uptake VO2max and the American College of Sports Medicine ACSM’s metabolic equations. The validity of using this methodology to elicit the recommended test duration of between 8 and 12 min was then evaluated. First, 83 subjects visited the laboratory once to perform a cycling (n=49) or walking (n=34) CPET to investigate the validity of the methodology. Second, 25 subjects (cycling group: n=13; walking group: n=12) performed a CPET on 2 separate days to test the reliability of CPET outcomes. Observed VO2max was 1.0 ml·kg−1·min−1 lower than predicted in the cycling CPET (P=0.001) and 1.4 ml·kg−1·min−1 lower in the walking CPET (P=0.001). Only one of the 133 conducted CPETs was outside the test duration range of 8–12 min. Test-retest reliability was high for all CPET outcomes, with intraclass correlation coefficients of 0.90 to 0.99. In conclusion, the non-exercise model is a valid and reliable method for establishing the final work rate of cycling and walking CPETs for eliciting test durations of between 8 and 12 min.
Keywords: cycling; walking; cardiopulmonary exercise testing; ergometry; physical fitness; reproducibility